1999
DOI: 10.1046/j.1442-2042.1999.06435.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus associated with bladder carcinoma? Analysis by polymerase chain reaction

Abstract: Background: The aim of the present study was to assess the possible etiologic role of human papillomaviruses (HPV) in bladder tumors. Methods: Forty-two fresh biopsy specimens from different grades and stages of bladder tumor cases and 10 normal bladder mucosa biopsies were studied. Specimens were analyzed by polymerase chain reaction (PCR) with HPV-specific general primer set for the detection of viral DNA. Polymerase chain reaction-positive samples were also tested with HPV 16-and 18-specific primers by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…53 Bladder squamous cell carcinoma very rarely shows basaloid/warty features, which is consistent with the infrequent finding of HPV in bladder squamous cell carcinoma. In fact, it was these morphological features that lead us to perform HPV studies initially.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…53 Bladder squamous cell carcinoma very rarely shows basaloid/warty features, which is consistent with the infrequent finding of HPV in bladder squamous cell carcinoma. In fact, it was these morphological features that lead us to perform HPV studies initially.…”
Section: Discussionsupporting
confidence: 83%
“…48,49 Other studies using the same methods yielded much lower rates of detection. 10,12,[50][51][52][53] Unfortunately, it is difficult to interpret the results because not all studies have analyzed non-lesional bladder tissue as control. For example, Anwar et al 9 detected the virus in 33% of healthy bladders, in contrast to Tekin, 53 who did not detect it in any of the 10 control cases.…”
Section: Discussionmentioning
confidence: 99%
“…Tekin et al, recently, stated that HPV did not seem to be related to the aetiology of bladder tumour due to its low prevalence reported in several previous studies (14), highlighting the possibility, as observed in cervical cancer studies by PCR, that positive results may be caused by superficial contamination of the tissue with HPV (15). Furthermore, Tekin et al suggested that in order to eliminate the possibility of contamination, future studies must be designed by using in situ PCR techniques, including samples taken from tumour and normal bladder mucosa in the same patient (14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tekin et al suggested that in order to eliminate the possibility of contamination, future studies must be designed by using in situ PCR techniques, including samples taken from tumour and normal bladder mucosa in the same patient (14). In the present study, in line with these suggestions, we analyzed samples taken both from tumour and urine, in order to eliminate the possibility of contamination and to demonstrate the feasibility and usefulness of HR-HPV DNA detected in the urine samples.…”
Section: Discussionmentioning
confidence: 99%
“…6 Only a few studies have reported koilocytosis in tumors of urinary bladder; the changes have been described more frequently in low grade tumors. 4,5 The aim of this study was to correlate koilocytosis with HrHPV DNA in urinary bladder carcinoma and to compare detection of koilocytosis on tissue sections and urine cytology.…”
mentioning
confidence: 98%